The Phenomenon of Dancing in Sholawat Assemblies Viewed from the Moral Perspectives of Ibnu Miskawaih and Jean-Paul Sartre - Fiqi Restu Subekti; Taufik Awan Wibowo (International Journal of Religion, Humanity and Cultural Heritage, 2025)
This research is motivated by the phenomenon of dancing in the sholawat gatherings. This issue has sparked a debate on whether or not dancing in these gatherings is acceptable, with opposing views from both proponents and opponents. The group in favor of this phenomenon argues that dancing in sholawat gatherings is a form of expressing joy. Meanwhile, the group opposed to it believes that dancing in such gatherings is inappropriate. Given this polemic, the aim of this research is to examine the phenomenon of dancing in sholawat gatherings from the moral philosophy perspectives of Ibn Miskawaih and Jean-Paul Sartre. This research uses a qualitative method with a literature study approach. Data collection is carried out through the review of relevant literature. The results of this study show that, according to Ibn Miskawaih's perspective, dancing in sholawat gatherings is an excessive act and thus can be considered immoral. This is because Ibn Miskawaih's moral concept is based on balance, avoiding both extreme excess and extreme deficiency. On the other hand, from Jean-Paul Sartre's perspective, dancing in sholawat gatherings is not an issue, as it is part of an individual's expression of their existence. According to Sartre, an individual expresses their existence through freedom in taking action.